2018
DOI: 10.1007/s13193-018-0852-5
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Assessment of Planning and Resection of Complex Bone Tumor Using Patient-Specific 3D Model

Abstract: Oncological interventions in thoracic cavity have some important problems such as choice of correct operative approaches depending on the tumor, size, extension, and location. In sarcoma surgery, wide resection should be aimed for the curative surgery. Purpose of this study was to evaluate pre-operative planning of patient-specific thoracic cavity model made by multidisciplinary surgeon team for complex tumor mass for oncological procedures. Patient's scans showed a large mass encroaching on the mediastinum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Segmentation using a global threshold based method on image intensity values is common in medical modeling (33,(40)(41)(42). However, it has limitations in dental modeling both because of the variability of the density of the structures within the maxillofacial region and the technical capabilities of the devices and algorithms used in dental imaging (13,33).…”
Section: Discussionmentioning
confidence: 99%
“…Segmentation using a global threshold based method on image intensity values is common in medical modeling (33,(40)(41)(42). However, it has limitations in dental modeling both because of the variability of the density of the structures within the maxillofacial region and the technical capabilities of the devices and algorithms used in dental imaging (13,33).…”
Section: Discussionmentioning
confidence: 99%
“…29 However, within spinal oncology, reports have been limited to small case series and case studies. 24,[30][31][32][33] Larger-scale studies are needed to fully understand the benefits of this technology in spinal oncological surgery.…”
Section: Lessonsmentioning
confidence: 99%
“…In all these clinical situations, an anatomical 3D model results in being helpful in surgical planning [ 12 , 13 ] and communication with the patients [ 14 , 15 ]. Moreover, it has been demonstrated that the anatomical 3D model helps reduce surgery duration [ 16 , 17 ] and intra-operative blood loss, allowing better surgical outcomes [ 18 ].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%